Pericardial Left Ventricular Assist Device (PALVAD) development via large animal and cadaveric models. (25th November 2020) - Premawardhana, A.D.P.E; Lodge, A.D; Sachdev, S; Karamanavi, E; Kotecha, D; Rothman, A.D; Samara-Ratna, P; Adlam, D
Abstract: Background: Cardiogenic shock complicates around 8% of acute myocardial infarctions with a significant short term mortality of 35–50%. Traditional mechanical circulatory support can improve cardiac output (CO) however they have significant adverse event profiles related to their position within the circulation, including but not limited to infection, stroke and embolism. PALVAD is an extra circulatory left ventricular assist device, designed to be implanted percutaneously., It provides cardiac support whilst sitting outside the circulatory system in the space between the pericardium and left ventricular (LV) free wall. The dual balloon system connects to an external pumping system via a drive line. The actuator balloon augments CO through ECG gated LV systolic compression and the positioning balloon sits against the pericardial surface dissipating this force across a large surface. Purpose: Assess device efficacy in a low CO state in a non-recovery porcine model. Understand device interactions with the left ventricle and pericardium in a cadaveric model. Methodology: Non-recovery porcine model experiments were conducted in three 40k-50g pigs at a large animal catheterisation facility. An Esmolol infusion was titrated to create a low output state. A Millar catheter was placed in the LV for simultaneous pressure and volume measurements and a Transonic flow probe was placed around the internal carotid for flow measurements. The device was inserted percutaneously and operated for a total of 4.7 hrs. For cadaveric experiments the device was inserted into a Thiel embalmed saline perfused cadaver following which detailed CT and MRI imaging was undertaken. Results: When target reduction in cardiac output was met PALVAD increased systolic pressure by 34%, stroke volume by 54%, CO by 53% and flow by 53%. There was no macroscopic evidence of epicardial or pericardial damage. Cadaveric imaging further informed optimal positioning of the device in relation to the LV free wall. Conclusions: PALVAD performance during low CO state in non-recovery porcine experiments is promising. Further recovery experiments, including histology assessment, are planed to evaluate safety and efficacy with longer term use to guide optimisation towards the eventual aim of a first-in-man trial. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): British Heart Foundation Translational Research Grant